2020
DOI: 10.2147/hiv.s275283
|View full text |Cite
|
Sign up to set email alerts
|

<p>Predictors of Metabolic Syndrome Among People Living with HIV in Gedeo-Zone, Southern-Ethiopia: A Case–Control Study</p>

Abstract: Background: Intensive access to antiretroviral therapy improved the prognosis of HIV. As a result, a non-communicable disease risk marker known as metabolic syndrome (MS) has emerged. It is a public health issue in sub-Saharan Africa including Ethiopia. However, there is little literature on predictors of MS among people living with HIV (PLHIVs) in the study area context. Purpose: To identify predictors of metabolic syndrome among PLHIVs, Gedeo Zone, Southern-Ethiopia. Methods: Health institutions-based unmatc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 42 publications
(81 reference statements)
1
9
1
Order By: Relevance
“…This is in agreement with other studies (41,73). In contrast, other studies found contradicting results (74,75). This may be due to differences in lifestyle.…”
Section: Discussionsupporting
confidence: 92%
“…This is in agreement with other studies (41,73). In contrast, other studies found contradicting results (74,75). This may be due to differences in lifestyle.…”
Section: Discussionsupporting
confidence: 92%
“…Prevalent MetS is also directly associated with stress 151 ; elevated intraocular pressure among people without glaucoma 152 ; sensorineural hearing loss among people with Turner syndrome 153 ; exposure to pesticides 154 ; exposure to antiretroviral therapy among adults living with HIV 155 ; elevated urine sodium 156 ; poor sleep characteristics 157 ; OSA 158 ; snoring 159 ; microalbuminuria 160 ; sarcopenia in middle-aged and older nonobese adults 161 ; visceral fat level 162 ; hypoactive sexual desire disorder among postmenopausal women 163 ; high heavy metal exposure 164 ; and high occupational noise exposure. 165…”
Section: Risk Factorsmentioning
confidence: 99%
“…Twenty-two studies reported impaired fasting glucose and Low HDL levels 22 , 24 , 26 , 28 32 , 34 44 , 46 48 , 24 studies reported high triglyceride levels, and 20 studies reported hypertension/raised BP and increased waist circumference/abdominal obesity 21 , 22 , 24 29 , 31 , 32 , 34 , 35 , 37 42 , 44 , 45 , 48 prevalence among PLHIV. The sub-components of MetS prevalence differed significantly among studies conducted in sub-Saharan Africa for PLHIV.…”
Section: Resultsmentioning
confidence: 99%